A study on customer’s awareness towards SUKIMI’S products / Mohd Norisham Mohamad Rosli - Mohamad Rosli, Mohd Norisham (2011)
Customers become aware towards products different based on the background, perception, experience learning and purchasing. The company must know the right strategies in order to attract the customers. The exposure to the product is important to create the awareness among customers. It is not easy to please every customer, because different customer will have different behavior and opinion. The examination of the factors that contribute to the customer’s awareness towards Sukimi’s products will give the answer that will fit based on objective of this study. How does that factor help customers to realize about the existence of the product in the market and how will it help in increasing the level of awareness. The objectives of this study are to evaluate the relationship between independent variables which is consists of advertising, sales promotion and personal selling with the customer awareness as the dependent variables and to identify the utmost and the least factors that contribute to the customer’s awareness towards Sukimi’s product whether advertising, sales promotion or personal selling. This research is mainly focused on the Sukimi’s customers who use the products and who may become potential customers. The data obtained from the questionnaire are being analyzed by using SPSS 14.0. In order to test the hypothesis, Correlation and Descriptive - Mean Test is being using and the result show that among three (3) of the variables do have the significant relationship with the factors that contribute to the customer’s awareness. Based from the results obtained in this study, researcher suggests some recommendations that can help SUKIMI GROUP to assist the current and future potential sales